Principles and practice of interventional pulmonology - Yarmus, Lonny; Ernst, Armin; Herth, Felix (Springer Nature Switzerland, 2026)
General Principles of Endoscopic Imaging -- The Bronchoscope: What is Available,.-Determining Selection, and How to Properly Care for the Instrument.-Bronchoscopy Unit Design for Advanced Procedures.-Quality Control Mechanism for Endoscopic Procedures.-Moderate and Deep Sedation Techniques.-Physiology of Fixed Airway Obstruction.-Airway Imaging -- Airway Anatomy.-Bronchoscopy Education.-Simulation for Endoscopy Training.-Assessment of Vocal Cord Function and Voice Disorders.-Conventional Biopsy Techniques.-Bronchoalveolar Lavage.-Cryobiopsy Technique, Training and Safety.-Cryobiopsy for ILD -- Radial EBUS and Real Time Sampling in the Periphery.-Linear Endobronchial Ultrasound -- Esophageal Ultrasound.-Narrow Band Imaging.-Confocal Imaging.-Optical Coherence Tomography.-Single Use Bronchoscopes.-Electromagnetic Navigational Bronchoscopy -- Transparenchchymal nodule access.-Robotic Assisted Bronchoscopy -- Transthoracic Needle Biopsy Techniques.-Rapid On Site Evaluation and Specimen Preparation -- Rigid Bronchoscopy.-Metallic Stenting -- Endobronchial Silicone Stents for Airway Management.-Y-Stenting Techniques -- Montgomery T-Tubes -- Medical Thoracoscopy/Pleuroscopy -- Pleurodesis.-Management Principles of Empyema.-Management of Malignant Pleural Effusions.-Percutaneous Tracheotomy.-Cricothyroidotomy.-Transtracheal Oxygen Catheter Placement and Management.-Percutaneous Endoscopic Gastrostomy (PEG) Tube Placement -- Whole-Lung Lavage.